The Effect of The Guided Discovery Learning Model on Students Mathematical Reasoning Skills - Stanley Gilbert Pangaribuan; Nurhanurawati; Agung Putra Wijaya (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This research was motivated by the gap between the importance of mathematical reasoning skills and the reality that such skills remained relatively low among students in Indonesia. The research aimed to determine the effect of the guided discovery learning model on students’ mathematical reasoning skills. This research was conducted at SMP Negeri 13 Bandar Lampung during the even semester of the 2025/2026 academic year. The eighth-grade students were distributed across 10 classes, two of which were honors classes, namely VIII-3 and VIII-4; therefore, these two classes were excluded from the research population. Consequently, the research population consisted of students in classes VIII-1, VIII-2, and VIII-5 through VIII-10, totaling 8 classes. The research sample was selected using cluster random sampling, with class VIII-2 as the control class and class VIII-7 as the experimental class. The design used was a pretest-posttest control group design. The data in this research consisted of quantitative data obtained through a mathematical reasoning skills test. Based on the results of data analysis using the Mann-Whitney-U test, it was found that the increasing in mathematical reasoning skills of students who participated in guided discovery learning was higher than students who participated in conventional learning. Thus, it can be concluded that the guided discovery learning model has an effect on students’ mathematical reasoning skills.